Design of a compact and wide-band monopole antenna - Fu, Bangye (Nanyang Technological University, 2023)
This dissertation presents two compact wide-band monopole antenna designs for the VHF/UHF frequency band, one is a two-dimensional (2-D) structure, and the other is a three-dimensional (3-D) structure. The 2-D design uses a tapered microstrip line feeding structure to improve the impedance matching. The patches of both layers are designed with slots to obtain a longer current path, improve the low-frequency performance, and reduce the antenna size. The bandwidth of this design is 0.21 GHz-0.96 GHz (128.2%) with VSWR less than 2.5, and this design has a compact electrical size of 0.31λmax×0.08λmax, where λmax is the free-space wavelength at the lowest operating frequency. The 3-D design is similar to a cylinder. A split cone structure is used as the central cone, and a slotted top-loading structure with meander lines is used to reduce the height and extend the current path. And a sleeve structure applied outside of the meander lines further increases the bandwidth. With the above structures, the antenna can achieve an operating bandwidth from 0.20 GHz-0.82 GHz (126.1%) with VSWR less than 2, and the electrical size is 0.08λmax×0.18λmax×0.18λmax.